Oxide thickness-dependent effects of source doping profile on the performance of single- and double-gate tunnel field-effect transistors - Nguyễn, Đăng Chiến (2023)
Operated by the band-to-band tunneling at the source-channel junction, the source engineering has been considered as an efficient approach to enhance the performance of tunnel field-effect transistors (TFETs). In this paper, we report a new feature that the effects of source doping profile on the performance of single- and double-gate germanium TFETs depend on equivalent oxide thickness (EOT). Based on the numerical simulations, it is shown that the effect of source concentration on the on-current is stronger with decreasing the EOT, particularly in the double-gate configuration due to the higher gate control capability. Importantly, when the EOT is decreased below a certain value, abrupt source-channel junctions are not only unnecessary, but gradual source doping profiles even improve the performance of TFETs because of the increase in vertical tunneling generation. With the continuous trend of scaling EOT, the oxide thickness-dependent effects of source doping profile should be properly considered in designing TFET devices.